Ethical hazards of modern, advanced medical technology in promoting euthanasia: a resolution from Islamic perspective - Malik, Mohammad Manzoor (International Islamic University Malaysia (IIUM), 2011)
Proponents of active euthanasia argue that in cases where the modern, advanced medical technology has prolonged death of many miserable terminally ill patients, active euthanasia can put end to their suffering; hence active euthanasia should be permissible. Against this line of thought, the researcher argues that much of the suffering which terminally ill patients go through occurs because of the misapplication of the advanced medical technology. Therefore, mishandled, mistreated, or over-treated patients become alleged subjects of debate on active euthanasia. It may be argued that consensus on permitting activeeuthanasia hasremained so far impossible because of ethical, cultural, and religious reasons, yet there is possibility of attaining consensus on the appropriate use and employment of advanced medical technology. This research argues that to avoid any legal and moral risks which may emerge from the inappropriate employment of the advanced medical technology to terminally ill patients, it is important to make the very initiation of advanced medical treatment in regard to the terminally ill patients subject to moral and legal analysis. This paper has basically two arguments: moral and preventive law arguments, and their links with Islamic perspective, leading eventually, to the Islamic perspective on the issue so as to suggest an ethically sound and rationally valid alternative.